The Midrashic imagination : Jewish exegesis, thought, and history - Fishbane, Michael, 1943- (Albany : State University of New York Press, 1993)
Annotation. Examines the broad range of Jewish interpretation from antiquity through the medieval and renaissance periods, focusing primarily on Midrash and midrashic creativity that includes the entire range of nonlegal interpretations of the Bible. Explores Midrash, considered as a literary and cultural form, from various perspectives, including mythmaking and parables. Paper edition (unseen), $16.95. Annotation copyright by Book News, Inc., Portland, OR.
(cont.) Can medieval storytelling help understanding Midrash? The story of Paltiel : a preliminary study on history and Midrash / Robert Bonfil -- History, story and collective memory : narrativity in early Ashkenazic culture / Ivan G. Marcus -- Sefer Yosippon : history and Midrash / Steven Bowman.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Midrash -- History and criticism; Bible. -- History -- Criticism, interpretation, etc., Jewish; Bible; RELIGION -- Judaism -- Sacred Writings; Midrash; Judaismo; Criticism, interpretation, etc; History